The Effect of Traditional Engklek on Gross Motor Development in 5–6-Year-Old Children at TK Pertiwi VII B - Sugiyah Sugiyah; Achmad Fadlan; Husin Husin (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Gross motor development is a fundamental component of early childhood education because it reflects children’s physical, cognitive, and socio-emotional readiness. This study aims to investigate the effect of the traditional engklek game on improving the gross motor skills of children aged 5–6 years. This quantitative study employed a pre-experimental one-group pretest–posttest design and was conducted at TK Pertiwi VII B, involving 15 Group B children. Data were collected through structured observation and documentation by focusing on four indicators: jumping on one foot, maintaining balance, body movement coordination, and agility. The engklek game intervention was implemented over six sessions. The results of the descriptive comparative analysis showed a positive shift in children’s developmental categories after the intervention. Before the intervention, most children were below the expected developmental standard, with 4 children categorized as Not Yet Developing and 5 children categorized as Starting to Develop. After the intervention, no children remained in the Not Yet Developing category, the Starting to Develop category decreased to 3 children, while 8 children reached the Developing as Expected category and 4 children reached the Developing Exceptionally Well category. This study concludes that the traditional engklek game can be effectively used as a physical stimulation medium to optimize gross motor development among young children. The findings contribute to early childhood education by highlighting the pedagogical value of traditional games as culturally relevant, engaging, and active learning media that may also help reduce the effects of sedentary lifestyles.